Patch Testing in Suspected Allergic Contact Dermatitis to Cosmetics - Pramod Kumar; Rekha Paulose (Dermatology Research and Practice)
Background. Increasing use of cosmetics has contributed to a rise in the incidence of allergic contact dermatitis (ACD) to cosmetics. It is estimated that 1–5.4% of the population is sensitized to a cosmetic ingredient. Patch testing helps to confirm the presence of an allergy and to identify the actual allergens which are chemical mixtures of various ingredients. Objectives. The aims of this study are to perform patch testing in suspected ACD to cosmetics and to identify the most common allergen and cosmetic product causing dermatitis. Methods. Fifty patients with suspected ACD to cosmetics were patch-tested with 38 antigens of the Indian Cosmetic Series and 12 antigens of the Indian Standard Series. Results. The majority (58%) of patients belonged to the 21–40 years age group. The presence of ACD to cosmetics was confirmed in 38 (76%) patients. Face creams (20%), hair dyes (14%), and soaps (12%) were the most commonly implicated. The most common allergens identified were gallate mix (40%), cetrimide (28%), and thiomersal (20%). Out of a total of 2531 patches applied, positive reactions were obtained in 3.75%. Conclusion. Incidence of ACD to cosmetics was greater in females. Face creams and hair dyes were the most common cosmetic products implicated. The principal allergens were gallate mix, cetrimide, and thiomersal.